Analysis of The Impacts of Family Ownership on a Company’s Costs of Debt - PERDANA, IDA BAGUS PUTRA; KUSUMASTUTI, RETNO (UI Scholars Hub, 2012)
There is an increasing trend among investors to consider Good Corporate Governance (GCG) in determining company incentives are to be invested in. Obviously, investors would prefer to make investments in companies that adopt Good Corporate Governance rather than otherwise. This view has eventually led to a belief that GCG can give added values not only to the adopting company, but also to the stakeholders. This research analyzes the impacts of family ownership and founding CEO/chairperson on a company’s costs of debt. This topic is chosen in consideration that there are still a lot of family-owned companies in Indonesia. The research uses a positivist-quantitative paradigm and the samples are 64 family-owned companies listed at the Indonesia Stock Exchange from 2007 to 2009. The research also uses a random effect model. The results of the research indicate that family ownership has positive but insignificant impacts, while founding CEO/chairperson has no impacts on a company’s costs of debt.